Controlling particle properties in YBa2Cu3O7−δ nanocomposites by combining PLD with an inert gas condensation system. (12th September 2017) - Sparing, M; Reich, E; Hänisch, J; Gottschall, T; Hühne, R; Fähler, S; Rellinghaus, B; Schultz, L; Holzapfel, B
Abstract: The critical current density J c in YBa 2 Cu 3 O 7 − δ thin films, which limits their application in external magnetic fields, can be enhanced by the introduction of artificial pinning centers such as non-superconducting nanoparticles inducing additional defects and local strain in the superconducting matrix. To understand the correlation between superconductivity, defect structures and particles, a controlled integration of particles with adjustable properties is essential. A powerful technique for the growth of isolated nanoparticles in the range of 10 nm is dc-magnetron sputtering in an inert gas flow. The inert gas condensation (IGC) of particles allows for an independent control of both the particle diameter distribution and the areal density. We report on the integration of such gas-phase-condensed HfO 2 nanoparticles into pulsed laser deposited (PLD) YBa 2 Cu 3 O 7 − δ thin film multilayers with a combined PLD-IGC system. The particles and the structure of the multilayers are analyzed by transmission electron microscopy on cross-sectional FIB lamellae. As a result of the IGC particle implementation, randomly as well as biaxially oriented BaHfO 3 precipitates are formed in the YBa 2 Cu 3 O 7 − δ thin films. With as few as three interlayers of nanoparticles, the pinning force density is enhanced in the low-field region.